ANALISIS KESULITAN MAHASISWA DALAM MENYIMAK MATERI AUDIO BAHASA PERANCIS PADA PERKULIAHAN COMPREHENSION ORALE - Rita; Yuliarti Mutiarsih; Yadi Mulyadi (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
There have been many studies related to the analysis of difficulty listening inforeign languages. The main obstacles of listening to foreign language audio materials includeunderstanding of pronunciation, speech speed, new vocabulary, and concepts or sentencepatterns. This study aims to (1) examine the results of the students' listening ability in thesecond semester, IV and VI of French audio material in Comprehension Orale learning inLanguage Laboratory, French Language Education Department FPBS UPI, and; (2) obtainingdata on the constraints affecting the students' listening ability. This research is a descriptiveresearch with a test of listening ability and questionnaire instrument with a total sample of 60students. The results showed that 50% of students in the second semester get the value oflistening test below the average score, even the fourth semester students who get test scoresbelow the average of 60%, and students of semester VI who get the value of the test listenedbelow the average as much as 55%. It implies that more than half of the respondents haveconstraints in both internal and external factors that make it difficult for them to listen toFrench audio material